A Monoclonal Antibody against p53 Cross-Reacts with Processing Bodies - Thomas, María Gabriela (Public Library of Science, 2012)
The p53 tumor suppressor protein is an important regulator of cell proliferation and apoptosis. p53 can be found in the nucleus and in the cytosol, and the subcellular location is key to control p53 function. In this work, we found that a widely used monoclonal antibody against p53, termed Pab 1801 (Pan antibody 1801) yields a remarkable punctate signal in the cytoplasm of several cell lines of human origin. Surprisingly, these puncta were also observed in two independent p53-null cell lines. Moreover, the foci stained with the Pab 1801 were present in rat cells, although Pab 1801 recognizes an epitope that is not conserved in rodent p53. In contrast, the Pab 1801 nuclear staining corresponded to genuine p53, as it was upregulated by p53-stimulating drugs and absent in p53-null cells. We identified the Pab 1801 cytoplasmic puncta as P Bodies (PBs), which are involved in mRNA regulation. We found that, in several cell lines, including U2OS, WI38, SK-N-SH and HCT116, the Pab 1801 puncta strictly colocalize with PBs identified with specific antibodies against the PB components Hedls, Dcp1a, Xrn1 or Rck/p54. PBs are highly dynamic and accordingly, the Pab 1801 puncta vanished when PBs dissolved upon treatment with cycloheximide, a drug that causes polysome stabilization and PB disruption. In addition, the knockdown of specific PB components that affect PB integrity simultaneously caused PB dissolution and the disappearance of the Pab 1801 puncta. Our results reveal a strong cross-reactivity of the Pab 1801 with unknown PB component(s). This was observed upon distinct immunostaining protocols, thus meaning a major limitation on the use of this antibody for p53 imaging in the cytoplasm of most cell types of human or rodent origin.